Legal Implications of The Formation of Tourist Villages on Collective Community Rights In The Management of Community Based Tourism Destinations - Meida Rachmawati; Diana Farid; Nadeem Sami Mohammad Altalahmeh; Annisa Elda Octivia; Anastasia Wahyu Murbani (al-Battar: Jurnal Pamungkas Hukum, 2025)
The establishment of tourist villages as a local development strategy has grown rapidly along with increasing awareness of the importance of community involvement in managing the tourism sector. Community-managed tourist villages serve not only as a means of economic development but also as an instrument for sustainable cultural and environmental preservation. However, this process poses legal challenges, particularly regarding the recognition and protection of community collective rights over local resources. The study aims to analyze the legal implications of the establishment of tourist villages on community collective rights, emphasizing the importance of participatory and equitable community-based governance. The method used is normative juridical research with a legislative and conceptual approach. The analysis was conducted on Law Number 6 of 2014 concerning Villages, Law Number 10 of 2009 concerning Tourism, and Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration Number 7 of 2023, which stipulates the priority use of village funds, including for the tourism sector. The research results indicate that despite the existence of a supporting legal framework, there is still a gap between normative regulations and implementation in the field. The lack of harmonization between national and local regulations, weak oversight of village funds, and the risk of commercializing village assets without community involvement are key challenges. Strengthening village regulations, establishing fair cooperation mechanisms, and active community involvement are needed to ensure that tourism villages truly become spaces for strengthening collective rights and village independence.